2022
DOI: 10.3390/jcm12010100
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Function in Long COVID-19 Using Heart Rate Variability: An Observational Cross-Sectional Study

Abstract: Background: Heart rate variability is a non-invasive, measurable, and established autonomic nervous system test. Long-term COVID-19 sequelae are unclear; however, acute symptoms have been studied. Objectives: To determine autonomic cardiac differences between long COVID-19 patients and healthy controls and evaluate associations among symptoms, comorbidities, and laboratory findings. Methods: This single-center study included long COVID-19 patients and healthy controls. The heart rate variability (HRV), a quant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
1
3
1
Order By: Relevance
“…Aranyo et al identified altered daytime pNN50 and SDNN as well as different frequency bands in COVID-19 patients suffering from inappropriate sinus tachycardia 17 . The longest HRV observation period after COVID-19 infection so far was approximately 3 months and reported both, time and frequency domain measures to be affected, the latter being comparable to our results 32 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Aranyo et al identified altered daytime pNN50 and SDNN as well as different frequency bands in COVID-19 patients suffering from inappropriate sinus tachycardia 17 . The longest HRV observation period after COVID-19 infection so far was approximately 3 months and reported both, time and frequency domain measures to be affected, the latter being comparable to our results 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Time domain measures, however, did not show any significant differences between PCS patients and controls during the 24 h period. These findings contrast reports in post-acute COVID-19 patients, which might be explained by either the various disease states (acute/post-acute/long-term), different kinetics/sensitivity of the various HRV parameters during the course of the disease or different HRV registration modes 32 . At least for the time course of the disease an effect on HRV parameters was identified since LF/HF ratio decreased significantly with increasing time after infection.…”
Section: Discussioncontrasting
confidence: 90%
“…Previous studies have shown the signi cance of HRV parameter reduction 39,40 and increased in ammatory parameters [41][42][43] in long-COVID individuals compared to the healthy population. Consistent with the results of this study regarding changes in the lower SDNN, TP, and VLF in the study subjects, the difference in results was not signi cant.…”
Section: Discussionmentioning
confidence: 95%
“…This is in line with our results which demonstrated low parasympathetic activity and a higher sympathetic activity. However, some studies found an autonomic unbalance but characterized by an increased parasympathetic tone in long COVID patients [75][76][77]. This difference could be explained by the numerous selection criteria for HRV analysis, and the variability of age and symptoms.…”
Section: Discussionmentioning
confidence: 99%